The Effect of Metal Powder on the Optical Properties of Polyvinyl Acetate - Sabbah, Shurooq; Hasan , Maher; Yehiaa , Baiddaa; Satar, Zenia (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2016)
In the present work, the effect of cupper particles onsomeoptical properties of Poly-vinyl acetate has been studied. For this purpose, many samples were prepared with different weight percentages of cupper particles. The samples were prepared by casting method with same thickness .The absorption has been recorded in the wavelength range (190-1100)nm.The optical constants (absorption coefficient, extinction coefficient, energy gap)of the indirect allowed and forbidden transition, real and imaginary dielectric constants have been determined . The optical constants are increase with increasing of cupper particles concentration. The energy gap decreased with increasing the weight percentages of cupper particle.